Characterization of Cowhage-induced Pruritus in Sensitive Skin: An Observational Laboratory Study - Ying Zuo (Society for Publication of Acta Dermato-Venereologica, 2021)
Sensitive skin is a prevalent syndrome, characterized by discomfort in response to mild stimuli, which impacts on quality of life. Pruritus is one of the major symptoms of sensitive skin. However, the pathomechanism of sensitive skin is insufficiently understood. As an experimental model for pruritus, the cowhage skin prick test might provide insight into the understanding of sensitive skin. This study aimed to specify the characteristics of cowhage-induced pruritus in sensitive skin. Female volunteers, 20 with sensitive skin and 20 controls, were recruited. Self-report questionnaires were distributed and the responses evaluated; moreover, alongside assessments by dermatologists, skin physiology assessments, lactic acid sting test, capsaicin test and cowhage skin challenge were performed. Pruritus in sensitive skin was perceived as more intense and longer-lasting than in normal skin, with different qualities of accompanying sensations. Cowhage skin challenge results showed moderate consistency with clinical assessments. The results suggest that cowhage skin challenge could be a new tool for the assessment of sensitive skin.